The Effect of Using a Digital Qur'an App on Students' Understanding of Tajwid - Umy Fitriani Nasution; Sultoni Trikusuma; Muhammad Yuga Raihansyah (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
This study aims to determine the effect of using a digital Qur’an app on the understanding of tajwid among students at Al-Razi Sinar Harapan Junior High School in Medan. The study was motivated by the fact that some students still struggle to understand and apply the rules of tajwid when reading the Qur’an. On the other hand, technological advancements have led to the development of various digital Qur’an applications equipped with tajwid features, audio recitations, and translations that have the potential to support the learning process. This study employed a quantitative approach with a correlational design. The study population consisted of 32 students in Class VII-1 at Al-Razi Sinar Harapan Junior High School in Medan, all of whom were included as the study sample using total sampling. Data collection was conducted through questionnaires, a tajwid comprehension test, observations, interviews, and documentation. The data were analyzed using normality tests and simple linear regression. The results indicate that the use of the digital Quran app has a positive and significant effect on students’ understanding of tajwid, with a regression coefficient of 0.675 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.812 indicates that 81.2% of the variation in students’ understanding of tajwid can be explained by the use of digital Qur’an applications. These findings suggest that digital Qur’an applications are effective as a learning medium for improving students’ understanding of tajwid.